Sustainability Reporting analysis of Triple Bottom Line Revelations in the Industrial Revolution 4.0 - Fadli, Syahir (STIEM BONGAYA, 2021)
Triple bottom line (TBL) and sustainability are two related constructs used interchangeably in the literature. A comprehensive review of the relevant literature has been conducted and has revealed inconsistent use of the term sustainability. Corporate Social Responsibility (CSR) is part of the responsibility and goodwill of the corporation/company and the company's voluntary interactions with their stakeholders. On the other hand, consistency in referring to the three lines simultaneously is built into the TBL structure because the constructs are explicitly based on the integration of social, environmental, and economic lines. However, because the company's concentration is more concentrated on the 4.0 industrial revolution, which is digitizing each process in the company so that the process of corporate social responsibility is hampered. The purpose of this paper is not to support arguments in favor of using one term over another but to provide an overview of the existence of both terms in the literature. With this in mind, researchers in business, management, and sustainability are encouraged to pay special attention to how they use these terms in their studies.